Merci Seigneur : os papéis das religiões diante do sofrimento de imigrantes haitianos em Cuiabá-MT - Coutinho, Dilvânia Costa (2018)
The migratory movements constitute a complex phenomenon of human mobility, implies rupture with basic references of the daily life and adaptation to the new socio-cultural context and can result in suffering. Solitude and the problems of everyday life can be chaotic, disorienting decision-making and losing sight of the dream, or even questioning its own existence, which leads many to seek a solution in a religious community . Religion has a functional and social sense, being more than a simple experience of faith, it offers an alternative way for insertion in the local community and social support for its installation and permanence. This paper discusses social support in the field of Collective Health, starting from references on popular religiosity and its interaction with the health of immigrants anchored in the concept of social support, popular religion and diffuse suffering in Victor Valla. This is a qualitative research with an ethnographic perspective in health, carried out with Haitian religious groups present in the vicinity of the Pastoral Center for Migrants in Cuiabá, which is a gateway to and welcome to these in the State, being a reference for humanitarian assistance and professional referral. The religious reinforce in their collective prayers, songs and dances their cultural belonging, while at the same time intensifying relations with the foreign community, attracting a large number of immigrant adherents. Some religious institutions supported this community, welcoming them by encouraging: 1) an experience of personal reconfiguration, due to social coexistence with peers and foreigners, or assuming functions in the ecclesiastical service, raising self-esteem and arousing the feeling of being useful giving new meaning to life; 2) a collective experience through religious reformulation concerning adaptation to the new socio-religious context that preserves certain rites, liturgies and songs. In the capital of Mato Grosso, the first Protestant ethnic institution formed by Haitians, was the Presbyterian, whose leader is a Haitian missionary sent to accompany his people spiritually who came from various regions and religions of the motherland. Soon other evangelical and Pentecostal institutions followed, which gave way to different times, equipment and instruments for meetings of study and worship in the native language. In addition to spiritual care, Haitian immigrants are socially and financially supported through donations such as food, clothing, furniture, appliances, rental payments, light and others; help in finding jobs; in times of need for health and transportation. These receptions are configured as religious social support that provide better mental health according to Valla.